`It has to hurt`: A phenomenological analysis of elite runners´ experiences in handling non-injuring running-related pain - Bluhm, K.; Ravn, S. (Qualitative Research in Sport, Exercise and Health, 2022)
Running can be a painful endeavour. In this article, we focus on four elite middle-distance runners` experience of non-injuring running-related pain, with the aim of better understanding how their handling of pain is a part of their expertise as elite athletes competing on an international level. The article employs phenomenological clarifications of bodily self-consciousness and pain in the analysis of an ethnographic fieldwork carried out during four months in a Danish elite middle-distance training group. The first author`s background in competitive running enabled him to draw on his own `insider` experiences as a runner to perform participant-observations and facilitate rich descriptions in both formal and informal interviews. The analysis indicates that a large part of the runners` training and racing relied on three overarching ways of handling pain. The runners possess a familiarity in dealing with the `acidic` pain experienced during short intervals and races, they `shuffle` with pain in order to enhance their performance, and they persistently ascribe context-dependant meaning to the experienced pain of running. Importantly, the runners continuously draw on this nuanced familiarity of their pained runner´s bodies while practicing and competing. We suggest that these ways of handling running-related pain can be understood as integral to their expertise as elite runners.